Sexual and environmental dimorphism of the frequency of significant correlations of body mass and height with feet features among 7-13-year-old adolescents - Mrozkowiak, Mirosław; Posłuszny, Mariusz (Journal of Education, Health and Sport, 2022)
The aim of the study is to demonstrate the sexual and environmental dimorphism of the frequency of significant correlations between body weight and height with selected feet features among 7–13-year-old children. Material and method. The research among 7-13-year-old children was being carried out over a period of 3 years in 6 semi-annual editions and allowed to register 16,462 observations of the value of 48 features describing feet, weight, and height of the body. The photogrammetric method was used to measure selected features. Conclusions Among 7-13-year-old children, the body height is more often associated with the features of the feet than the body weight. Among girls, the proportions of the frequency of body height correlations are similar to the percentage of boys, where body weights are more frequent. The mass and body height shows more frequent associations with feet features among children living in the city than among children from the countryside. The most frequent significant correlations between body weight and height and the features of the feet occur among boys living in the city. Whereby the percentage of body weight correlations in the rural environment is very low. The frequency of body weight and height correlations exceeds that percentage of correlations among girls, who live in the city than in those from rural environment.